The amelioration of thermal comfort inside traditional housing in Menaa City-Algeria - Djafri, Riadh; Mohamed Osman, Mariana; Rabe, Noor Suzilawati (Malaysian Institute Of Planners, 2020)
The traditional housing in Algeria are designed to adapt to the surrounding condition and desert climate. The internal housing layout and thermal comfort plays a significant role in the Algerian traditional housing design and standards. The historical, cultural, religion and climate of Algeria have significant influence on the design of its houses. This study of houses in the City of Menaa in Batna, Algeria, explained the traditional design of houses of the people of Amazigh, particularly Chaoui in the building of homes and shelters. Today, the condition of traditional houses in Menaa Batna, is far from satisfactory because the city has suffered lack of economic investment by the central government which resulted in significant deterioration of its traditional housing condition that lead to discomfort in term of thermal especially during winter. This research aims to analysis the current condition of these traditional houses and to propose improvement in term of thermal comfort to the occupier of these houses. The study used mixed methods namely literature review where the researcher used comparative approach from international case study; and descriptive analyses based on the questionnaire and observations. The results of the analyses enabled the researcher to recommend improvement to the condition of the houses using integrated solutions and techniques. These recommendations were designed to achieve a modern and environmentally acceptable thermal comfort in winter season for the houses, without losing the traditional architectural features of these old houses.